Towards a Conceptual Approach on the Connections of Urban Metabolism and Entropy with the Human Habitat - José Alejandro Barón-Hernández; José Alfonso Baños-Francia; Peter Rijnaldus Wilhelmus Gerritsen; Sandra Quijas (World)
The complexity of urban areas has motivated the search for integrative approaches. This paper addresses three topics—human habitat, urban metabolism, and urban entropy—to explore their links within the context of urban territory and sustainability. The lack of approaches, outlooks, and synergies motivates the search for an integrated conceptual framework, what I originated as a review of published works to contribute an interdisciplinary and multiscale outlook. From reviewing 41 articles, published from 1960 to 2020, definitions were extracted, original concepts were identified, synthetic definitions were formulated, and basic elements were identified to be integrated into a first synthetic approach, both illustrative and schematic. Eighteen binding key concepts, which were derived from 83 definitions, were incorporated into the proposed conceptual framework. We suggest that the human habitat, urban metabolism, and urban entropy are strongly interrelated, confirming the utility of the proposed conceptual framework and showing the potential to generate methodological approaches that integrate one or several conceptual elements that comprise it. Demonstrating the explicit bond between definitions, concepts, and components integrated systematically into the proposed conceptual framework is innovative in the field of scientific investigation, considering its applicability to public policy, resource management, or sustainable urban planning.